Dose‐response association of early‐life antibiotic exposure and subsequent overweight or obesity in children: A meta‐analysis of prospective studies. (29th July 2021) - Meng, Xin; Zhu, Yi; Di, Hongkun; Zhang, Mingye; Feng, Jing; Xu, Minzhi; Xia, Wenqi; Tian, Qingfeng; He, Yan; Gan, Yong; Lu, Zuxun
Summary: The objective of this study is to investigate the dose‐response relationship between antibiotic exposure in early life and the risk of subsequent overweight or obesity. Electronic databases were searched from inception to December 2020. Prospective studies that reported the odds ratios (ORs) of childhood overweight or obesity for three or more quantitative categories of antibiotic exposure were identified. A random‐effect model was used to pool the ORs and 95% confidence intervals (CIs). Generalized least squares and restricted cubic splines were used to explore the dose‐response association. A total of 12 sets of results from 10 articles involving 427, 453 participants were included in this meta‐analysis. The pooled OR for increased risk of overweight or obesity was 1.30 in high‐level antibiotic exposure (95% CI: 1.20 to 1.41) and 1.06 in low‐level antibiotic exposure (95% CI: 1.02 to 1.10), as compared with children who never exposed to antibiotics. There was a logarithmic‐curve relationship between early‐life antibiotic exposure and the risk of subsequent overweight or obesity. The OR was 1.08 (95% CI: 1.06 to 1.11) for one prescription, 1.16 (95% CI 1.11 to 1.21) for two prescriptions, 1.24 (95% CI: 1.16 to 1.32) for three prescriptions, 1.30 (95% CI: 1.20 to 1.41) for four prescriptions, and less than a 5% increase for more prescriptions. Early‐life antibiotic exposure is associated with the risk of childhood overweight or obesity in a dose‐response manner. Further studies are needed to confirm our results.